The impact of camaderie on customer satisfaction and loyalty in the hotel industry - TAN, Huiping Josephine (Institutional Knowledge at Singapore Management University, 2018)
In the hotel industry, the relationship between customer satisfaction and loyalty has always been ambiguous, as a satisfied hotel guest may not necessarily be loyal. Loyalty is of greater interest to the hotel industry as it translates to more business opportunities. The primary purpose of this study is to investigate how camaraderie and emotional customer satisfaction can predict potential service loyalty. Empirical tests of the relationship between camaraderie, emotional satisfaction and loyalty had never been conducted before in the hotel industry. The findings of this research suggest that camaraderie has a direct and significant relationship to the four phases of loyalty, cognitive, affective, conative and action loyalty. This research will contribute to the body of knowledge on customer satisfaction, camaraderie, and loyalty and provides theoretical and applied suggestions for the hotel industry.